2005
DOI: 10.1128/jcm.43.4.2004-2008.2005
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing Directly on DNA from Clinical Samples and a Cultured Isolate To Investigate Linked Fatal Pneumococcal Disease in Residents of a Shelter for Homeless Men

Abstract: Two apparently linked fatal cases of pneumococcal meningitis were investigated. Pneumolysin PCR performed on blood and cerebrospinal fluid was positive in a culture-negative case. A second case yielded Streptococcus pneumoniae from blood culture. Multilocus sequence typing performed on DNA extracted from case 1 (specimens) and case 2 (isolate) revealed identical sequence types (ST53) substantiating the link between them. CASE REPORTTwo male residents of a shelter for homeless people, each with a history of exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
(18 reference statements)
1
13
0
Order By: Relevance
“…Serotype 8 pneumococci have also been responsible for such outbreaks [25,40]. In the present study of 121 pneumococcal isolates, nonhemolytic pneumolysin variants were found only in serotypes that have been associated with outbreak disease.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Serotype 8 pneumococci have also been responsible for such outbreaks [25,40]. In the present study of 121 pneumococcal isolates, nonhemolytic pneumolysin variants were found only in serotypes that have been associated with outbreak disease.…”
Section: Discussionmentioning
confidence: 46%
“…In addition, serotype 1 pneumococci have a high attack rate and are rarely isolated from nasopharyngeal carriage [23,24]. Serotype 8 pneumococci have also been associated with linked cases of disease [25].…”
mentioning
confidence: 99%
“…In this baseline study we detected ST53 as the main clone found in IPD caused by serotype 8. This clone has been reported as a virulent clone 38 and at present is the dominant clone in serotype 8-related IPD in Scotland. 39 Jefferies et al found a pneumolysin allele 5 in ST53 that could facilitate clonal expansion of serotype 8, which would be of particular concern.…”
Section: Discussionmentioning
confidence: 88%
“…The samples were tested for the S. pneumoniae autolysin and pneumolysin genes using the method previously described for dual target testing of clinical samples [3]. Non-culture MLST was attempted on any dual-target PCR-positive samples following the method recently described by Birtles et al [4].…”
Section: Non-culture Testing Of Samplesmentioning
confidence: 99%